Immanuel Wallerstein's Theory of the Capitalist World-System - Darius Žiemelis (Lietuvos Istorijos Studijos)
One of the most significant tendencies in the development of Western historiography and social sciences in the last three decades has been the consolidation of a new multidisciplinary field of inquiry, comparative historical sociology (CHS). Reinhard Bendix, Charles Tilly, and Immanuel Wallerstein can be considered parents/creators of CHS in the U.S.A. The theory of the Capitalist World System (CWS), initiated by the American sociologist and historian I. Wallerstein (b. 1930), who started his career researching the contemporary history of Africa, is one branch of the CHS. This theory was formulated in opposition to Eurocentrism, which is characterized by a belief in the endless (linear) progress of European civilization and which discounts other (non-European) cultures. Wallerstein's popularity and influence in Western social sciences reached its zenith in the 1970s and 1980s, so that while perhaps coming late in the game, nonetheless knowledge and acquaintance with the ideas of this author can be useful for the conceptual renewal of modern Lithuanian historiography and for the investigation of problems in the socio-economic history of Central and Eastern Europe. The main strength of the CWS's approach is the possibility to expand historical thinking to regional and global perspectives in reply to the challenges facing social, political, and geopolitical reality and to interpret the history of every region in the historical context of local and world (meta) civilization.